International cooperation in response to environmental threats and emergencies - Tolochko, Olga N. (Journal of the Belarusian State University. Law, 2025)
International cooperation in rapid response to environmental threats and emergencies is an important area of protection of the population and territory of the Republic of Belarus. In this regard, it is extremely important to improve the norms of international and national law, as well as the integration law of the Eurasian Economic Union in the area under consideration. The object of the study is public relations arising in the process of international cooperation to counteract, prevent and eliminate the consequences of environmental threats and emergencies. The purpose of the study is to analyse the existing institutional and contractual system of counteracting environmental threats and emergency situations, as well as to develop practical proposals for improving the rules of law. As a result of the study, the main trends in the development of legal regulation in the field of counteracting environmental threats and emergency situations were identified, proposals for improving the legislation in the studied area were developed. The scope of application is the law of the Eurasian Economic Union, the legislation of the Republic of Belarus, the practice of applying these rules in the process of international cooperation on environmental threats and emergency situations.